Experimental serpentinization of iron-rich olivine (hortonolite): Implications for hydrogen generation and secondary mineralization on Mars and icy moons. (15th October 2022) - McCollom, Thomas M.; Klein, Frieder; Moskowitz, Bruce; Solheid, Peter
Abstract: Serpentinization of olivine-rich ultramafic rocks is recognized to have been widespread across the solar system throughout its history, with substantial implications for the chemical and physical properties of planetary lithospheres, atmospheric compositions, and astrobiology. One especially significant product of serpentinization is molecular hydrogen (H2 ), whose generation is closely linked to the oxidation of Fe as serpentinization proceeds. While numerous experimental simulations of serpentinization have been conducted over the years, these studies have been performed almost exclusively using reactant minerals that contain relatively high Mg and low Fe contents representative of terrestrial mantle rocks. In contrast, very few studies have been conducted with the more Fe-enriched mineral compositions that may predominate on other solar system bodies. In this study, an experiment was conducted to investigate mineral alteration and H2 generation during serpentinization of Fe-rich olivine (hortonolite; Fo∼62 ) at 230 °C and 35 MPa. After 3500 h of reaction, ∼55 % of the hortonolite reacted to secondary minerals composed of serpentine (chrysotile) and magnetite. Chrysotile contained proportionally less Fe than the original hortonolite, reflecting the partitioning of some Fe into magnetite; however, it contained substantially more Fe than serpentine precipitated from alteration of Mg-rich, Fe-poor terrestrial mantle olivine (Fo∼90 ) under the same reaction conditions. Reaction of hortonolite also produced more than four times as much magnetite as Mg-rich olivine. Generation of H2 occurred steadily throughout the experiment, with more than five times as much H2 generated per mole of hortonolite reacted than observed for Fe-poor olivine at the same conditions. The results suggest that serpentinization of Fe-rich ultramafic rocks on Mars and other planetary bodies may have a substantially greater capacity to generate H2 and to precipitate magnetite than their Fe-poor terrestrial counterparts, which would enhance their potential to support H2 -based biological communities, contribute to atmospheric warming, and augment local magnetic signatures in planetary lithospheres.